THE EFFECT OF MATHEMATICAL SELF-EFFICACY ON THE STUDENTS' LEARNING OUTCOMES OF TEACHING PRACTICE PLACEMENT (PPL) - Sri Sulasteri; Fitriani Nur; Suharti Suharti (Faculty of Tarbiyah and Teacher Training Universitas Islam Negeri Alauddin Makassar, 2020)
Abstract:This study aimed to investigates the effect of Mathematical self-efficacy on the students’ learning outcomes of Teaching Practice Placement (PPL). This research used ex-post-facto with simple paradigm design. The population were 80 students’ Department of Mathematics Education. Sampling technique used was saturated sample so that all the members of the population selected. The instruments used were questionnaire and documentation. The data were analyzed by using descriptive and inferential statistical analysis. The findings indicate that the average of the students' self-efficacy is 95.66 which is categorized as ‘fair’, the students’ learning outcomes of teaching practice placement is 3.87 which is categorized as ‘A’, and the regression gained through regression testwas Y = 2.359 + 0.016X. Thus, there is significant effect of self-efficacy on the students’ learning outcomes of Teaching Practice Placement.Abstrak:Penelitian ini bertujuan untuk menyelidiki efek self-efficacy matematika pada hasil belajar mahasiswa dari Praktek Pengalaman Lapangan (PPL). Jenis penelitian ini menggunakan ex-post-facto dengan desain paradigma sederhana. Populasi terdiri dari 80 mahasiswa Jurusan Pendidikan Matematika. Teknik pengambilan sampel yang digunakan adalah sampel jenuh, sehingga semua anggota populasi dipilih. Instrumen yang digunakan terdiri dari kuesioner dan dokumentasi. Data dianalisis menggunakan analisis statistika deskriptif dan inferensial. Hasil penelitian ini menunjukkan bahwa rata-rata self-efficacy siswa adalah 95.66 dengan kategori 'sedang', hasil belajar siswa dari penempatan praktik mengajar adalah 3.87 dengan kategori 'A', dan persamaan regresi diperoleh melalui uji regresi, yaitu Y = 2.359 + 0.016X. Dengan demikian, ada pengaruh yang signifikan dari self-efficacy terhadap hasil belajar mahasiswa dari Praktek Pengalaman Lapangan.